2020
DOI: 10.1111/acem.13980
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of a Quasi‐experimental Regional Opioid Safety Prescribing Program in Veterans Health Administration Emergency Departments

Abstract: Background The Veterans Health Administration (VHA) Opioid Safety Initiative (OSI) was implemented in 2013 and was associated with a 25% relative decrease in the dispensing of opioids. Although emergency department (ED) providers play a role in the initiation and continuation of opioids, the incumbent OSI did not target EDs. Objective The goal of this feasibility study was to leverage the existing VHA OSI and test a novel ED‐based quality improvement (QI) program to decrease opioid prescribing in multiple ED s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…Of these, 180 were kept for full-text review, and 63 unique studies were included in the review ( Figure 1 ). 12 , 27 , 28 , 29 , 30 , 31 , 32 , 35 , 36 , 37 , 39 , 40 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 180 were kept for full-text review, and 63 unique studies were included in the review ( Figure 1 ). 12 , 27 , 28 , 29 , 30 , 31 , 32 , 35 , 36 , 37 , 39 , 40 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , …”
Section: Resultsmentioning
confidence: 99%
“…Seven interventions used different approaches to examine opioid prescribing or prescribing activities after the AD interventions. 6 , 24 , 26 , 27 , 30 , 31 , 35 In providers that self-reported an intention to change versus none-to-moderate intention to change, Saffore et al compared mean total opioid and high-dose opioid prescriptions per clinician per month before and after the AD intervention. 6 The authors found significantly fewer mean total opioid (−1.48, 95% CI −2.48 to −0.47) and high-dose opioid (−0.50, 95% CI −0.69 to −0.31) prescriptions per clinician per month in the intention to change group compared with the no-to-moderate intention to change group.…”
Section: Resultsmentioning
confidence: 99%
“…Dieujuste et al reported that their multifaceted intervention of AD, audit, feedback and addition of electronic medical record prescribing resources resulted in the ED opioid prescribing rate decreasing by 47% over 21 months. 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the pilot suggested that our program was associated with accelerating the rate at which ED prescribing rates decreased. 11 In addition, the pilot found that ED-based QI initiatives in VHA facilities are a feasible practice. As we work to develop and implement the next 2 phases of the QI program, a major consideration is to identify facilitators and address any existing barriers to the implementation of naloxone distribution (aim 2) and MATinitiation (aim 3) programs for treatmentnaïve patients from VHA EDs.…”
mentioning
confidence: 99%